Development and Characterization of a Novel Chitosan-Based Dental Composite for Restorative Applications - Sajjad, Syeda Tooba; Urooj, Komal; Arif , Amna; Shafaqat, Kinza; Hussain, Sajid; Ikram, Amna Mehwish (Journal of Neonatal Surgery, 2025)
Background: Dental composites have become a common treatment in restorative procedures, although traditional forms of dental composites do not have any antibacterial properties, which is the cause of secondary caries. Chitosan is a natural polysaccharide that has biocompatibility and antimicrobial properties, and thus makes it a promising additive in restorative composites. Objective: To formulate and describe a new dental composite based on chitosan and to assess the mechanical and antimicrobial properties. Methods: This is an in vitro experimental study that was carried out for six months. Control composite and chitosan-incorporated composite (1%, 3%, 5%) specimens were made as per the ISO standards. Analysis of data was done using SPSS v26; the level of significance was taken at p ≤ 0.05. Discussion: The flexural strength was reduced to 100.6 ± 5.5 MPa (5% chitosan) as compared to the control, which was 110.5 ± 5.2 MPa. Reductions in compressive strength and hardness were also modest. The chitosan content was found to greatly enhance antibacterial activity with an inhibition zone of 4.2 ± 0.8 mm (1%), 6.8 ±0.9 mm (3%), and 9.1 ±1.0 mm (5%), whereas no activity was observed in controls. Conclusion: Chitosan-based dental composites have a stronger antibacterial activity and yet can maintain a satisfactory mechanical performance in the clinical environment, which means that they can be used as bioactive restorative materials. .